Pengaruh Latihan Target Box Terhadap Ketepatan Shooting Futsal Atlet Di Ekstrakurikuler SMPN 11 Kota Bekasi - Falih, Januar Ilham; Candra, Juli; 'Ala, Faridatul; Pasaribu, Ahmad Muchlisin Natas; Ningrum, Desy Tya Maya (JURNAL ILMIAH NUSANTARA, 2025)
Futsal is quite popular among various age groups, including children, teenagers, and adults. In futsal, mastery of basic techniques is crucial because every player is required to have good technical skills without exception. The purpose of this study was to determine the effect of target box training on the shooting accuracy of futsal athletes in the extracurricular program at SMPN 11 Bekasi City. The research method used was an experimental method with a One Group Pretest-Posttest Design, aimed at determining the effect of target box training on futsal shooting accuracy. The results of this study indicate that the implementation of target box training significantly influences the improvement of futsal shooting accuracy among extracurricular athletes at SMPN 11 Kota Bekasi.